Health-Conscious Energy Management for Fuel Cell Hybrid Electric Vehicles Based on Prognostics-Enabled Decision-Making - Yue, Meiling; Jemei, Samir; Zerhouni, Noureddine (IEEE transactions on vehicular technology, 2019)
In this paper, a health-conscious energy management strategy based on prognostics-enable decision-making in the framework of prognostics and health management has been proposed for the studied fuel cell hybrid electric vehicle. Fuzzy logic controllers have been optimized by off-line genetic algorithm under different degradation states and corresponding confidence factors have been allocated to them according to the on-line health state classification results. Then, the parameters of the off-line tuned fuzzy logic controllers are fused together based on Dempster-Shafer data fusion theory in order to calculate the on-line used fuzzy rules. Simulation results have showed that the proposed approach can mitigate the power source degradation and save the economic cost.